Municipal Economic Development and Greenhouse Gas Emissions in Brazil - Pietrafesa, Pedro Araújo; Souza, Laumar Neves de; Pietrafesa, José Paulo (Fronteira: Journal of Social, Technological and Environmental Science, 2026)
Climate change is closely linked to the economic and social dynamics of countries and subnational units. In general, studies analyzing this relationship tend to use nation-states as their unit of observation. This study aims to contribute to the literature by focusing on a more decentralized unit, Brazilian municipalities. Brazil is a country of continental dimensions and heterogeneity in development patterns across its states. The objective of this article is to analyze how the economic development of Brazilian municipalities affects greenhouse gas emissions, considering the disparity in subnational economic dynamism across the country. The methodology employed was a two-level multilevel model. Since the data was organized by municipal CO2e emissions nested within each state, except for the Federal District, this justified the choice of a multilevel modeling approach. The results indicate that economic complexity, Gross Domestic Product, level of social vulnerability, deforestation, and the Sebrae Index of Local Development at the state level were significant variables in explaining CO2e emissions in Brazilian municipalities. Additionally, the growth rate of municipal emissions was lower in states that already had high average emissions compared to those with low average emissions. It is concluded that the state in which a municipality is located matters when analyzing the relationship between economic complexity and CO2e emissions.